Inflation and fiscal policy: Is there a threshold effect in the fiscal reaction function? - Clémence Briodeau; Cristina Checherita-Westphal (European Central Bank (ECB), 2023)
This paper estimates a fiscal reaction function (FRF) framework for euro area countries to test for the impact of changes in inflation on fiscal policy. We find evidence of non-linear short-term effects of HICP inflation on the primary balance after controlling for other relevant factors. Over the period 1999-2022, we unveil an inverse U-turn relationship and an inflation turning point - beyond which its short-term (contemporaneous) impact on the primary balance starts being negative - at somewhat above 4% for the sample of mature euro area economies (EA-12, first twelve EA members) and around 6% for the whole sample of euro area countries in 2022 (EA-19). Using an alternative measure of "inflation surprise" (available for the period 2003-2022) yields robust results in the larger EA-19 sample and lowers the threshold to just below 5%. In terms of channels, the non-linear effects are found to propagate through both the primary expenditure and the revenue ratio (more robustly through the former) in the EA-12 sample, while only the combined effect on the primary balance seems to prevail for EA-19. These results reflect primarily the most recent high inflation episode and indicate that in such conditions inflation can be costly for public finance flows even in the shorter run.
Keywords: H60; E62; E31; C33; 330; fiscal reaction function; inflation; euro area; panel models